2015
DOI: 10.1159/000381540
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Morphology in Patients with Orthostatic Intolerance

Abstract: Background: We evaluated the cortical morphology in patients with orthostatic intolerance. Methods: Thirty patients with orthostatic intolerance, as well as age- and sex-matched normal controls, were enrolled in this study. We divided the patients into orthostatic hypotension (n = 22) and postural tachycardia syndrome (n = 8) groups based on their response to a head-up tilt table test. We analyzed whole-brain T1-weighted MRI images using FreeSurfer 5.1. The measures of cortical morphology were compared between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…Another study observed right insular atrophy in patients with neuro‐cardiogenic syncope with positive response to the head‐up tilt test, implicating the role of right insular dysfunction in the pathophysiologic mechanism underlying neuro‐cardiogenic syncope (Kim et al., ). In addition, we previously demonstrated that the cortical thickness of orbitofrontal, pericalcarine, postcentral, inferior temporal, and lateral occipital cortex significantly changed in patients with orthostatic hypotension but not in patients with postural tachycardia syndrome (Shin et al., ). These discrepancies could be caused by the different subjects and imaging methods used, or produced by the different vulnerable brain structures to hypo‐perfusion according to various subjects.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Another study observed right insular atrophy in patients with neuro‐cardiogenic syncope with positive response to the head‐up tilt test, implicating the role of right insular dysfunction in the pathophysiologic mechanism underlying neuro‐cardiogenic syncope (Kim et al., ). In addition, we previously demonstrated that the cortical thickness of orbitofrontal, pericalcarine, postcentral, inferior temporal, and lateral occipital cortex significantly changed in patients with orthostatic hypotension but not in patients with postural tachycardia syndrome (Shin et al., ). These discrepancies could be caused by the different subjects and imaging methods used, or produced by the different vulnerable brain structures to hypo‐perfusion according to various subjects.…”
Section: Discussionmentioning
confidence: 94%
“…Second, postural tachycardia syndrome is a form of dysautonomia. A study using voxel‐based morphometry revealed diminished gray matter volume within the frontal gyrus in patients with postural tachycardia syndrome (Shin et al., ). Third, chronic complex regional pain syndrome is a debilitating pain condition accompanied by autonomic abnormalities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study of 22 patients with orthostatic hypotension, defined as a sustained reduction in blood pressure greater than 20 mm HG systolic or greater than 10 mm HG diastolic within 3 min of standing or a tilt table test [ 2 ], and 8 patients with POTS using T1-weighted MRI, the cortical thickness in the right hemisphere, including the medial orbitofrontal, peri-calcarine, post-central, inferior temporal, and lateral occipital cortex, and in the peri-calcarine cortex of the left hemisphere was thinned in patients with orthostatic hypotension, but not POTS, compared to normal controls [ 23 ].…”
Section: Neuroimaging Studies In Pots Other Autonomic Disorders and mentioning
confidence: 99%